Legal Protection for Consumers in Transations E-Commerce by Era Digital - Musmualim Musmualim; Fokky Fuad; Suartini Suartini (Green Publisher Indonesia, 2024)
The rapid development of information and communication technology (ICT) has brought significant changes in various aspects of life, including in the world of commerce in the form of e-commerce. Although e-commerce offers many conveniences and advantages, it also presents multiple risks and potential law violations for consumers. This study aims to analyze the legal framework that regulates consumer protection in e-commerce transac-tions in Indonesia. This research uses a normative juridical method. The data was collect-ed through a literature review of legal literature, laws and regulations related to e-commerce, and recent research reports highlighting consumer protection issues. The data collected will be analyzed qualitatively. The results of the study show that legal protection for consumers in e-commerce transactions in the digital era is regulated in Law Number 8 of 1999 concerning Consumer Protection. Consumer protection includes effective dispute resolution mechanisms, such as mediation or arbitration, as well as legal procedures if necessary. This aims to ensure that consumers have fair and fast access to resolving is-sues with manufacturers or service providers. Efforts to strengthen legal protection for consumers need to be carried out on an ongoing basis by various parties, including the government, business actors, and the community.